A subthreshold current‐sensing ΣΔ modulator for low‐voltage and low‐power sensor interfaces. (8th October 2014) - Katic, Nikola; Kazi, Ibrahim; Tajalli, Armin; Schmid, Alexandre; Leblebici, Yusuf
Summary A continuous‐time (CT) ΣΔ modulator for sensing and direct analog‐to‐digital conversion of nA‐range (subthreshold) currents is presented in this work. The presented modulator uses a subthreshold technique based on subthreshold source‐coupled logic cells to efficiently convert subthreshold current to digital code without performing current‐to‐voltage conversion. As a benefit of this technique, the current‐sensing CT ΣΔ modulator operates at low voltage and consumes very low power, which makes it convenient for low‐power and low‐voltage current‐mode sensor interfaces. The prototype design is implemented in a 0.18 µm standard complementary metal‐oxide semiconductor technology. The modulator operates with a supply voltage of 0.8 V and consumes 5.43 μW of power at the maximum bandwidth of 20 kHz. The obtainable current‐sensing resolution ranges from effective number of bits (ENOB) = 7.1 bits at a 5 kHz bandwidth to ENOB = 6.5 bits at a 20 kHz bandwidth (ENOB). The obtained power efficiency (peak FoM = 1.5 pJ/conv) outperforms existing current‐mode analog‐to‐digital converter designs and is comparable with the voltage‐mode CT ΣΔ modulators. The modulator generates very low levels of switching noise thanks to CT operation and subthreshold current‐mode circuits that draw a constant subthreshold current from the voltage supply. The presented modulator is used as a readout interface for sensors with current‐mode output in ultra low‐power conditions and is also suitable to perform on‐chip current measurements in power management circuits. Copyright © 2014 John Wiley & Sons, Ltd.